Motivation Peculiarities of Self-Education of Students in Modern Conditions - - Nham Ngoc Tan (Peoples' Friendship University of Russia (RUDN University), 2012)
The development of modern informative and communicative technologies is reflected in the education system, providing the conditions of formation of the education of the new type meeting the requirements of the development and self-development of personality in the modern society. The influence of informative and communicative technologies on the motivation of self-education of students is revealed in the article.